2022
DOI: 10.1073/pnas.2209139119
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the ancestral mammalian karyotype and syntenic regions

Abstract: Decrypting the rearrangements that drive mammalian chromosome evolution is critical to understanding the molecular bases of speciation, adaptation, and disease susceptibility. Using 8 scaffolded and 26 chromosome-scale genome assemblies representing 23/26 mammal orders, we computationally reconstructed ancestral karyotypes and syntenic relationships at 16 nodes along the mammalian phylogeny. Three different reference genomes (human, sloth, and cattle) representing phylogenetically distinct mammalian superorder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0
11

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 78 publications
0
38
0
11
Order By: Relevance
“…While outliers in the PCA could represent migrants from other genetic populations, more samples would help investigate their structure in more detail. Within large geographical regions, it appears gene flow is generally high in bowhead whale groups (within the Canadian Arctic [28], East Greenland [30], and western Arctic [82]). Bowhead whales are capable of large movements [83] and separate populations have overlapped summer distributions.…”
mentioning
confidence: 99%
“…While outliers in the PCA could represent migrants from other genetic populations, more samples would help investigate their structure in more detail. Within large geographical regions, it appears gene flow is generally high in bowhead whale groups (within the Canadian Arctic [28], East Greenland [30], and western Arctic [82]). Bowhead whales are capable of large movements [83] and separate populations have overlapped summer distributions.…”
mentioning
confidence: 99%
“…These data suggested that ancestral amniotes had both ETV2 and FLI1B genes in a genomic locus linked to COX6B1 , RBM42 , and HAUS5 genes, with subsequent loss of ETV2 and FLI1B in birds ( Fig 1D ), of FLIB in mammals ( Fig 1D ), and of ETV2 in turtles (UCSC genome browser gateway; data not shown). Linkage of ETV2 gene to RBM42 and HAUS5 genes was seen in amphibia (Tibetan frog, X. levis , and X. tropicalis ) and to RBM42 gene in teleost fish (zebrafish, medaka, and tetraodon) (UCSC genome browser gateway), suggesting that syntenic organization of ETV2 and its neighboring genes in ancestral amniotes was the result of rearrangements of homologous syntenic blocks during tetrapod evolution ( Sacerdot et al, 2018 ; Damas et al, 2021 , 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…This result also further rationalizes the chromosome number variation in this genus. Chromosome polymorphisms within species in natural populations of vertebrates are far less common and are believed to be temporary transitions during chromosomal evolution (Damas et al 2021, 2022). Likewise, the Zanthoxylum may be experiencing chromosomal evolution.…”
Section: Discussionmentioning
confidence: 99%